2020
DOI: 10.1101/2020.04.15.20066068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The socio-economic determinants of the coronavirus disease (COVID-19) pandemic

Abstract: The magnitude of the coronavirus disease pandemic has an enormous impact on the social life and the economic activities in almost every country in the world. Besides the biological and epidemiological factors, a multitude of social and economic criteria also govern the extent of the coronavirus disease spread in the population. Consequently, there is an active debate regarding the critical socio-economic determinants that contribute to the resulting pandemic. In this paper, we contribute towards the resolutio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 77 publications
12
123
1
3
Order By: Relevance
“…Closely related to our study are The Economist (2020), Stojkoski et al (2020) and Castex et al (2020). The Economist's review uses a sample of U.S. states focusing on the case-fatality rate.…”
Section: Mortality Ratessupporting
confidence: 78%
“…Closely related to our study are The Economist (2020), Stojkoski et al (2020) and Castex et al (2020). The Economist's review uses a sample of U.S. states focusing on the case-fatality rate.…”
Section: Mortality Ratessupporting
confidence: 78%
“…Our results support the WHO recommendations, to increase testing and track of COVID-19 cases in all countries, given its de nitive impact to reduce the CFR. In line with Stojkoski, et al (2020) we found that the countries expenditure on health as well as their development level is positively related to CFR, cases and deaths, which cannot be interpreted as causation, but it is indicating that developing countries a not tracking enough cases yet. In consequence, we claimed that there is an under identi cation of data given the positive correlation between cases and deaths and testing, meaning that testing is still reactive and with little identi cation of asymptomatic, which is also highlighted by the OECD (2020) and the WHO (2020).…”
Section: Discussionsupporting
confidence: 83%
“…Although it was anticipated by several researchers initially that the density of the population had a positive correlation with the spread of COVID-19 [39,40,41,42,43]], some recent studies show that the assumption might not be completely evident [44,32]. Health expenditure by the government was identified as a significant determinant of deaths caused from COVID-19 [45,46], whereas topographical locations along with their climatic circumstances were detected as prominent factors for the diffusion of the virus [47]. Although the temperature has been observed to be a relevant factor of COVID-19 transmission according to the results of some studies [48,49,50], there are some counterarguments as well [51,52].…”
Section: Prediction Models and Their Componentsmentioning
confidence: 99%